Novel hysteresis effect in ultrathin epitaxial Gd₂O₃ high-k dielectric - Nazarov, A.N.; Gomeniuk, Y.V.; Gomeniuk, Y.Y.; Lysenko, V.S.; Gottlob, H.D.B.; Schmidt, M.; Lemme, M.C.; Czernohorsky, M.; Ostenc, H.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Charge trapping in ultrathin high-k Gd₂O₃ dielectric leading to appearance of hysteresis in C–V curves is studied by capacitance-voltage, conductance-frequency and current-voltage techniques at different temperatures. It was shown that the large leakage current at a negative gate voltage causes the reversible trapping of the positive charge in the dielectric layer, without electrical degradation of the dielectric and dielectricsemiconductor interface. The capture cross-sections of the hole traps are around 10⁻¹⁸ and 2 × 10⁻²⁰ cm² . The respective shift of the C–V curve correlates with a “plateau” at the capacitance corresponding to weak accumulation at the silicon interface.